PERLINDUNGAN HUKUM ATAS PALA ACEH SELATAN SEBAGAI PRODUK INDIKASI GEOGRAFIS - NANDA MAULINA SAFIRA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Jelly Leviza, SH, MHum Geographical indication is defined as an indication symbolizing the place or good and/or products by which geographical environmental factor including the factors of nature, human and the combination of both contribute a particular reputation, quality and characteristics. The agricultural products in Aceh Province that have been registered as the product of geographical indications are gayo coffee, gayo oranges and Aceh patchouli, while the nutmegs of South Aceh has not yet been registered as the geographical indications product and is not yet legally protected. The good reputation and quality of the nutmeg of South Aceh is well-known in national and international because it has special characteristic. Considering that the nutmeg had ever been rejected by foreign countries because it was contaminated by kerosene by irresponsible pary that wanted to take profits from its reputation. It is necessary to register the nutmeg to be protected, in geographical indications. Keyword: Registration, Legal Protection, Geographical Indications